Answer:
![y=-\frac{4}{3}x^{2}](https://tex.z-dn.net/?f=y%3D-%5Cfrac%7B4%7D%7B3%7Dx%5E%7B2%7D)
Step-by-step explanation:
The given parabola is a parent function, that is, it's the simplest form of a parabola.
The first transformation is about a reflection across the x-axis, this means that we need to multiplied the squared factor by a negative signed, that is
![y=-x^{2}](https://tex.z-dn.net/?f=y%3D-x%5E%7B2%7D)
This represents a parabola reflected across the x-axis.
The second transformation is about a scale factor of 4/3, this means that the function has to be multiplied by this factor to obtain the transformation. The expression would be
![y=-\frac{4}{3}x^{2}](https://tex.z-dn.net/?f=y%3D-%5Cfrac%7B4%7D%7B3%7Dx%5E%7B2%7D)
Therefore, this final expression represents the function reflected across the x-axis and scaled by a factor of 4/3.